Nutritional and microbial evaluation of some frozen marine fish species sold in selected local government areas of Kano State, Nigeria (Acta Scientiarum. Animal Sciences, 2025)
This study was carried out to evaluate the nutritional compositions and microbial load of some frozen marine fish species sold in Kano State, Nigeria. A total of 81 samples comprising 27 each of Atlantic herring (Clupea harengus), Atlantic mackerel (Scomber scombrus) and Atlantic horse mackerel (Trachurus trachurus) were purchased from three sampling areas: Bichi, Dambatta and Gwarzo. They were analysed for proximate, mineral compositions, and microbial load using standard procedures. Results indicated that the highest crude protein content, 21.51% was recorded in T. trachurus from Dambatta, while the mineral composition revealed that C. harengus recorded the highest sodium content, 1.69 mg Kg-1, from Bichi. The highest free fatty acids 2.07 ± 0.18% was observed in T. trachurus from Gwarzo. The results of the microbial population elucidated that T. trachurus had the highest Salmonella spp. count of 4.22 x 106cfu g-1 from Dambatta. The Escherichia coli of 3.22 x 106cfu g-1 recorded in S. scombrus from Dambatta was the highest. All the microbial loads parameters were affected by the species, but not the collection station. The microbial load recorded in this study did not exceed the recommended limit of x106 to 107cfu g-1 of bacteria load safe for human consumption. The study therefore recommends T. trachurus as the best for consumption in the study area, due to its higher protein composition and the lowest microbial load.